HUBUNGAN STRES DENGAN KUALITAS HIDUP PENDERITA DIABETES MELLITUS TIPE 2 - Mhd. Zainuddin ' '; Wasisto Utomo; Herlina ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract Diabetes mellitus is a diasease who will be happen on a life time. The changes in lifestyle, medication and treatment who must be followed is a cause stress the patient type 2 diabetes mellitus. The aim of this research is to determine the relationship between stress and quality of life in patient type 2 diabetes mellitus. The research method used a descriptive correlation design with cross sectional approach. The research was conducted in the impatient unit Arifin Achmad Pekanbaru hospital on 30 respondents who experienced type 2 diabetes mellitus using accidental sampling technique based on the inclusion criteria. Research instrument used a questionnaire was adoption based Depression Anxiety Stress Scale to measure level of stress and WHOQOL-BREEF to measure quality of life. The analysis used univariate and bivariate analysis using Kolmogorov-Smirnov. The result showed that there is a relationship between stress and quality of life in patient type 2 diabetes mellitus with degree ρ = 0,024 < α = 0,05. This research concluded that there is a relationship between stress and quality of life in type 2 diabetes mellitus. Based on the result of this research, it is expected for nurse give provide nursing care and stress management for patient with type 2 diabetes mellitus to minimize the stress level, because the severe stress level can also decreased quality of life and aggravate the patient illness especially diabetes mellitus. Keywords: Type 2 diabetes mellitus, stress, quality of life